SUPERVISI PEMBELAJARAN TEMATIK PADA GURU DI SD NEGERI DADAPSARI SEMARANG - Rahayuningsih, Lusia Endang (2011)
The objectives of this research are to describe (1) the characteristics of principal activity in supervision of thematic learning of teacher at SD N Dadapsari Semarang, (2) the characteristics of teacher activity in supervision of thematic learning of teacher at SD N Dadapsari Semarang, and (3) the characteristic of follow up activity in supervision of thematic learning of teacher at SD N Dadapsari Semarang. This is qualitative research. The research is conducted in SD N Dadapsari Semarang. The main subjects in this research are principal, and teacher. Data collecting method used interview, observation, and documentation. Data analyses used arrange analysis in site. Data validity test used credibility, transferability, conformability, and dependability. The research's result shows that (1) the principal's activity in supervision of thematic learning of teacher is according to the rule and watching classroom condition. Principal is doing instrument preparation, records of supervision result that is done before, and also select teacher. Principal is doing supervision with class visiting technique that is done incidental. Principal is evaluate teacher performance in learning activity, cooperative behaving, and involve thematic learning activity so that student is not disturb with principal existence in teaching learning activity. (2) Teacher activity in supervision of thematic learning is according to learning stages that compiled in RPP and it is not influenced by principal's existence. Teacher doing learning activity as usual by compiling learning means, opening learning activity, few teacher is keeping their attitude in learning activity, doing evaluation and also closed the learning activity. (3) The follow up activity in supervision of thematic learning of teacher at SD N Dadapsari is done by based on supervision's result and give solution toward the difficulty in teacher learning. Principal is held follow up meeting by individually and generally according to principal's report about learning activity that is done by teacher. Principal is give opportunity to teacher to correct the learning activity that is done in individual meeting. In general meeting, teacher is given solution to solve the learning problem such as following study compare activity, workshop, training, and also KKG. School is providing fund to development Smart Park so that teacher can doing learning activity out side classroom.